Strategies to avoid intraoperative blood transfusion. Issue 2 (February 2022) - Swift, Adam; Lucero, Harriet; Hamilton, Christopher; Carroll, Craig
Abstract: Transfusion of donor blood is sometimes unavoidable during the surgical episode. However, it is associated with adverse outcomes. Interventions that improve preoperative haemoglobin and reduce the need for donor transfusion a have positive impact upon outcome. The principle of reducing the need for transfusion is known as patient blood management (PBM) and incorporates three pillars (anaemia management, limitation of blood loss and use of alternatives to donor blood products, and restrictive transfusion triggers) when used in combination appear the most effective way to limit the impact of surgical blood loss.